Cyber Law and Interpersonal Relations: A Comprehensive Review - Patama, Ilham Muhammad Jalu; Rosnawati, Emy; Nurhayati (Proceedings of The ICECRS, 2023)
This data article investigates the intersection of Cyber Law and Interpersonal Relations through an analysis of 60 scholarly articles in the Law category, utilizing Lens.org's search platform. By focusing on keywords "Cyber Law" and "Interpersonal Relations," the study highlights the surge in cyber-related crimes affecting digital relationships. Noteworthy findings reveal active institutions like the University of Warwick, a prolific publication year in 2017, and dominant fields like Sociology, led by influential authors such as Michael Rowe. Australia emerges as a key region, with Queensland University of Technology as a prominent publisher. The data underscores the need for heightened awareness regarding cyber law violations in social media, aiming to promote responsible digital behavior and combat detrimental actions in interpersonal connections.Highlights : Analysis of 60 scholarly articles reveals the surge in cyber-related crimes impacting digital relationships. Identification of key institutions, prolific publication years, dominant fields of study, and influential authors within the domain. Emphasis on Australia's prominence in this field and the imperative need for responsible digital conduct to mitigate harmful actions in interpersonal relations. Keywords: Cyber Law, Interpersonal Relations, Digital Crimes, Social Media, Responsible Conduct